Grade 11 Public Schools Students’ Knowledge and Challenges in Learning the Sociocultural History of Negros Occidental - Galvez, John Allan A.; Bual, Joel M. (Philippine Social Science Journal, 2025)
To address the necessity of grasping regional dynamics within the Understanding Culture, Society, and Politics (UCSP) course, this study assessed the knowledge of Negros Occidental’s socio-cultural history and learning challenges among 278 Grade 11 public school students. Using a validated quantitative design, findings revealed that students possess generally low knowledge across social and cultural domains, including politics, economics, values, and norms. Identified challenges included a reliance on textbooks over local examples, students’ weak social science foundations, and resource-deficient learning environments. Consequently, the study emphasizes the urgent need to integrate local history into the curriculum, improve teacher professional development, and create targeted learning activity sheets to bridge these gaps, serving as a basis for future, larger-scale research.